Efficient synthesis of pyrazolopyridines containing a chromane backbone through domino reaction - Navari, Razieh; Balalaie, Saeed; Mehrparvar, Saber; Darvish, Fatemeh; Rominger, Frank; Hamdan, Fatima; Mirzaie, Sattar (Beilstein Journal of Organic Chemistry, 2019)
An efficient approach for the synthesis of pyrazolopyridines containing the aminochromane motif through a base-catalyzed cyclization reaction is reported. The synthesis was carried out through a three-component reaction of (arylhydrazono)methyl-4H-chromen-4-one, malononitrile, primary amines in the presence of Et3N at room temperature. However, carrying out the reaction under the same conditions without base led to a fused chromanyl-cyanopyridine. High selectivity, high atom economy, and good to high yields in addition to mild reaction conditions are the advantages of this approach.
Keywords: chromane; domino reaction; fused heterocyclic skeletons; pyrazolopyridines

(untitled) - Cabrele, C.; Reiser, O. (J. Org. Chem., 2016)

(untitled) - Blass, B. (ACS Med. Chem. Lett., 2012)

(untitled) - Panda, S.; Roy, A.; Deka, S. J.; Trivedi, V.; Manna, D. (ACS Med. Chem. Lett., 2016)

Multicomponent Reactions in Organic Synthesis - Zhu, J.; Wang, Q.; Wang, M.-X. (Wiley-VCH, 2015)

Science of Synthesis, Multicomponent Reactions I - Müller, T. J. J. (George Thieme Verlag, 2014)

Science of Synthesis Multicomponent Reactions II - Müller, T. J. J. (George Thieme Verlag, 2014)

Domino Reactions in Organic Synthesis - Tietze, L. F.; Brasche, G.; Gericke, K. M. (Wiley-VCH, 2006)

Domino Reactions: Concepts for Efficient Organic Synthesis - Tietze, L. F. (Wiley-VCH, 2014)

(untitled) - Tietze, L. F. (Chem. Rev., 1996)

(untitled) - Khan, T. A.; Fornefeld, T.; Hübner, D.; Vana, P.; Tietze, L. F. (Org. Lett., 2018)

(untitled) - Gaspar, A.; Matos, M. J.; Garrido, J.; Uriarte, E.; Borges, F. (Chem. Rev., 2014)

(untitled) - Pratap, R.; Ram, V. J. (Chem. Rev., 2014)

(untitled) - Keri, R. S.; Budagumpi, S.; Pai, R. K.; Balakrishna, R. G. (Eur. J. Med. Chem., 2014)

(untitled) - Shaabani, A.; Hooshmand, S. E. (RSC Adv., 2016)

(untitled) - Balalaie, S.; Esmaeilabadi, H.; Mehrparvar, S.; Rominger, F.; Hamdan, F.; Bijanzadeh, H. R. (SynOpen, 2018)

(untitled) - Balalaie, S.; Derakhshan-Panah, F.; Zolfigol, M. A.; Rominger, F. (Synlett, 2018)

(untitled) - Teimouri, M. B.; Akbari-Moghaddam, P.; Golbaghi, G. (ACS Comb. Sci., 2011)

(untitled) - Michailidou, M.; Giannouli, V.; Kotsikoris, V.; Papadodima, O.; Kontogianni, G.; Kostakis, I. K.; Lougiakis, N.; Chatziioannou, A.; Kolisis, F. N.; Marakos, P.; Pouli, N.; Loutrari, H. (Eur. J. Med. Chem., 2016)

(untitled) - Matsuda, D.; Kobashi, Y.; Mikami, A.; Kawamura, M.; Shiozawa, F.; Kawabe, K.; Hamada, M.; Oda, K.; Nishimoto, S.; Kimura, K.; Miyoshi, M.; Takayama, N.; et al. (Bioorg. Med. Chem. Lett., 2016)

(untitled) - de Mello, H.; Echevarria, A.; Bernardino, A. M.; Canto-Cavalheiro, M.; Leon, L. L. (J. Med. Chem., 2004)

(untitled) - Mousseau, J. J.; Fortier, A.; Charette, A. B. (Org. Lett., 2010)

(untitled) - Gunasekaran, P.; Perumal, S.; Menéndez, J. C.; Mancinelli, M.; Ranieri, S.; Mazzanti, A. (J. Org. Chem., 2014)

(untitled) - Witherington, J.; Bordas, V.; Gaiba, A.; Garton, N. S.; Naylor, A.; Rawlings, A. D.; Slingsby, B. P.; Smith, D. G.; Takle, A. K.; Ward, R. W. (Bioorg. Med. Chem. Lett., 2003)

(untitled) - Lee, S.; Park, S. B. (Org. Lett., 2009)

(untitled) - Straub, A.; Benet-Buckholz, J.; Fröde, R.; Kern, A.; Kohlsdorfer, C.; Schmitt, P.; Schwarz, T.; Siefert, H.-M.; Stasch, J.-P. (Bioorg. Med. Chem., 2002)

(untitled) - Kendre, D. B.; Toche, R. B.; Jachak, M. N. (Tetrahedron, 2007)

(untitled) - Abet, V.; Nuñez, A.; Mendicuti, F.; Burgos, C.; Alvarez-Builla, J. (J. Org. Chem., 2008)

(untitled) - Beutner, G. L.; Kuethe, J. T.; Kim, M. M.; Yasuda, N. (J. Org. Chem., 2009)

(untitled) - Ghaedi, A.; Bardajee, G. R.; Mirshokrayi, A.; Mahdavi, M.; Shafiee, A.; Akbarzadeh, T. (RSC Adv., 2015)

(untitled) - Bogza, S. L.; Kobrakov, K. I.; Malienko, A. A.; Perepichka, I. F.; Sujkov, S. Y.; Bryce, M. R.; Lyubchik, S. B.; Batsanov, A. S.; Bogdan, N. M. (Org. Biomol. Chem., 2005)

(untitled) - Galvez, J.; Castillo, J.-C.; Quiroga, J.; Rajzmann, M.; Rodriguez, J.; Coquerel, Y. (Org. Lett., 2014)

(untitled) - Pettus, L. H.; Wurz, R. P.; Xu, S.; Herberich, B.; Henkle, B.; Liu, Q.; McBride, H. J.; Mu, S.; Plant, M. H.; Saris, C. J. M.; Sherman, L.; Wong, L. M.; et al. (J. Med. Chem., 2010)

(untitled) - Kumar, N. R.; Poornachandra, Y.; Swaroop, D. K.; Dev, G. J.; Kumar, C. G.; Narsaiah, B. (Bioorg. Med. Chem. Lett., 2016)

(untitled) - Zimmerman, J. R.; Myers, B. J.; Bouhall, S.; McCarthy, A.; Johntony, O.; Manpadi, M. (Tetrahedron Lett., 2014)

(untitled) - Gunasekaran, P.; Indumathi, S.; Perumal, S. (RSC Adv., 2013)

(untitled) - Heller, S. T.; Natarajan, S. R. (Org. Lett., 2007)

(untitled) - Balalaie, S.; Mirzaie, S.; Nikbakht, A.; Hamdan, F.; Rominger, F.; Navari, R.; Bijanzadeh, H. R. (Org. Lett., 2017)

(untitled) - Balalaie, S.; Shamakli, M.; Nikbakht, A.; Alavijeh, N. S.; Rominger, F.; Rostamizadeh, S.; Bijanzadeh, H. R. (Org. Biomol. Chem., 2017)

(untitled) - Balalaie, S.; Ramezani Kejani, R.; Ghabraie, E.; Darvish, F.; Rominger, F.; Hamdan, F.; Bijanzadeh, H. R. (J. Org. Chem., 2017)

(untitled) - Balalaie, S.; Vaezghaemi, A.; Zarezadeh, N.; Rominger, F.; Bijanzadeh, H. R. (Synlett, 2018)

(untitled) - Plaskon, A. S.; Grygorenko, O. O.; Ryabukhin, S. V. (Tetrahedron, 2012)

(untitled) - Słomiak, K.; Łazarenkow, A.; Chęcińska, L.; Kusz, J.; Ochocki, J.; Nawrot-Modranka, J. (Molecules, 2018)

(untitled) - Wang, G.; Chen, M.; Wang, J.; Peng, Y.; Li, L.; Xie, Z.; Deng, B.; Chen, S.; Li, W. (Bioorg. Med. Chem. Lett., 2017)

(untitled) - Shen, H.; Xie, Z. (J. Am. Chem. Soc., 2010)